Mechanical Dyssynchrony Precedes QRS Widening in ATP‐Sensitive K+ Channel–Deficient Dilated Cardiomyopathy. Issue 6 (5th December 2013) - Yamada, Satsuki; Arrell, D. Kent; Kane, Garvan C.; Nelson, Timothy J.; Perez‐Terzic, Carmen M.; Behfar, Atta; Purushothaman, Saranya; Prinzen, Frits W.; Auricchio, Angelo; Terzic, Andre
Abstract : Background: Contractile discordance exacerbates cardiac dysfunction, aggravating heart failure outcome. Dissecting the genesis of mechanical dyssynchrony would enable an early diagnosis before advanced disease. Methods and Results: High‐resolution speckle‐tracking echocardiography was applied in a knockout murine surrogate of adult‐onset human cardiomyopathy caused by mutations in cardioprotective ATP‐sensitive K + (KATP ) channels. Preceding the established criteria of cardiac dyssynchrony, multiparametric speckle‐based strain resolved nascent erosion of dysfunctional regions within cardiomyopathic ventricles of the KATP channel–null mutant exposed to hemodynamic stress. Not observed in wild‐type counterparts, intraventricular disparity in wall motion, validated by the degree, direction, and delay of myocardial speckle patterns, unmasked the disease substrate from asymptomatic to overt heart failure. Mechanical dyssynchrony preceded widening of the QRS complex and exercise intolerance and progressed into global myocardial discoordination and decompensated cardiac pump function, precipitating a low output syndrome. Conclusions: The present study, with the use of high‐resolution imaging, prospectively resolved the origin and extent of intraventricular motion disparity in a KATP channel–knockout model of dilated cardiomyopathy. Mechanical dyssynchrony established as an early marker of cardiomyopathic disease offers novel insight into the pathodynamics of dyssynchronous heart failure.